SPATIAL DISTRIBUTION AND CORRELATION ANALYSIS OF THE HEALTH RESOURCE IN GUANGDONG - WANG, Lian-tong (Journal of Research for Christianity in China (JRCC), 2025)
This article explores in depth the issue of how God speaks to people, the purpose, the content, and the number of words in Genesis of Bible, by using correlation analysis and semantic analysis method in statistics. The results show that the Bible records a total of 38 God-to-human speeches in the Bible Genesis, involving 17 individuals and 6 different appearances. Correlation analysis showed that people's attitude toward God's command was positively related to the number of words God spoke to this person. Obedient people receive more words from God, and God speaks less to disobedient people. Semantic analysis shows that God is most concerned about the topic of "descendants," which accounting for 63% contents of all God's speaking verses. The analysis of the appearance shows that apart from "the Bible does not mention the appearance," God speaks most "in the dream" of people. Thees laws is consistent with Job 33: 15-18 and John 14:21. The conclusion of this article provides a reference for the correct interpretation of how did God speaks to people, and has significance to promote the truth.
Keywords: God; Bible; Genesis; Way of God speaking; Communication of God and people